Effectiveness of Intravitreal Bevacizumab Monotherapy in the Treatment of Retinopathy of Prematurity: An Experience of a Tertiary Care Hospital in Central Punjab (Journal of Fatima Jinnah Medical University, 2025)
ABSTRACTBackground: Retinopathy of prematurity (ROP) is a leading cause of preventable childhood blindness especially in low- and middle-income countries where neonatal survival has improved but screening remains limited. Intravitreal anti VEGF agents offer a promising alternative to laser photocoagulation. The objective of this study was to determine the frequency of ROP in preterm neonates and assess the effectiveness of intravitreal bevacizumab IVB monotherapy for Stage 3 ROP.Methods: This prospective interventional study was conducted at Sir Ganga ram hospital Lahore from September 2021 to March 2023. A non-probability consecutive sampling was used to recruit eligible preterm neonates (
Keywords: Retinopathy of Prematurity; Bevacizumab; Infant; Premature